2019
DOI: 10.1038/s41598-019-46833-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CuO nano-particles on stimulating production of actinorhodin in Streptomyces coelicolor by transcriptional analysis

Abstract: In this research, antibiotic-producing bacteria, Streptomyces coelicolor ( S. coelicolor ) M145, was exposed to copper oxide (CuO) particles to investigate the effects of nano-particles (NPs) on antibiotic production. Results showed that a higher yield of antibiotics was obtained with smaller particle sizes of CuO NPs. When exposed to 10 mg/L of 40 nm CuO NPs, the maximum amount of actinorhodin (ACT) obtained was 2.6 mg/L after 144 h, which was 2.0-fold greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Pioneering studies successfully used such materials to streamline the morphology of eukaryotic filamentous fungi and enhance the formation of enzymes (Driouch, Hänsch, Wucherpfennig, Krull, & Wittmann, 2012; Driouch, Roth, Dersch, & Wittmann, 2010; Kaup, Ehrich, Pescheck, & Schrader, 2008), polyketides, and alcohols (Etschmann et al, 2015). More recently, several studies suggested that microparticles are also beneficial to enhance product formation in filamentous prokaryotes (Holtmann et al, 2017; Liu, Tang, Wang, & Liu, 2019; Ren et al, 2015; J. Walisko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies successfully used such materials to streamline the morphology of eukaryotic filamentous fungi and enhance the formation of enzymes (Driouch, Hänsch, Wucherpfennig, Krull, & Wittmann, 2012; Driouch, Roth, Dersch, & Wittmann, 2010; Kaup, Ehrich, Pescheck, & Schrader, 2008), polyketides, and alcohols (Etschmann et al, 2015). More recently, several studies suggested that microparticles are also beneficial to enhance product formation in filamentous prokaryotes (Holtmann et al, 2017; Liu, Tang, Wang, & Liu, 2019; Ren et al, 2015; J. Walisko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was hypothesized that altering the native species in a plant's environment would impact the antagonistic behavior of various Streptomyces [46]. For instance, a study used four distinct plant species: Andropogon gerardii, Schizachyrium scoparium, Lespedeza capitata, and Lupinus perennis, to highlight the reduced susceptibility of A. gerardii to the plant pathogens when grown in monoculture of Streptomyces species [47].…”
Section: Field Trials With Streptomycesmentioning
confidence: 99%
“…Particle size, nanoparticle concentration, and precursor type are all likely to affect the antibacterial effect. Studies have made clear that CuO NPs affect cell activity in a concentration‐dependent manner 102,103 . In the experiment with Streptomyces aeruginosa M145 as strain, the smaller the particle size of CuO NPs, the stronger the antibacterial effect in a single cell, which shows a noticeable size effect 102 .…”
Section: Fight Arb With Alternative Weaponsmentioning
confidence: 99%
“…Studies have made clear that CuO NPs affect cell activity in a concentration‐dependent manner 102,103 . In the experiment with Streptomyces aeruginosa M145 as strain, the smaller the particle size of CuO NPs, the stronger the antibacterial effect in a single cell, which shows a noticeable size effect 102 . Javadhesari et al 104 found out that compared to NPs derived by CuSO 4 ·5H 2 O, the CuO NPs prepared with CuCl 2 ·2H 2 O as precursor showed more potent antibacterial activity.…”
Section: Fight Arb With Alternative Weaponsmentioning
confidence: 99%